Explaining the urban premium in Chinese cities and the role of place-based policies. (October 2020) - Howell, Anthony; Liu, Chong; Yang, Rudai
This paper relies on the empirical framework introduced in Combes et al. (2012) to address the following main questions: (a) what are the relative contributions of agglomeration and selection forces expected to drive the urban productivity premium previously observed in Chinese cities, and (b) to what extent does the industrial parks and zones (IPZs) program, a popular place-based policy, simultaneously influence selection and agglomeration mechanisms? The main findings are as follows. First, both agglomeration and selection forces are observed in larger, denser Chinese cities, indicating that earlier studies that failed to take into account selection likely overestimate the effect of agglomeration economies. Second, after taking into account non-random site selection based on matching, the IPZs program intensifies both agglomeration and selection forces, although the results depend strongly on who administers the program. The empirical findings highlight a theoretical connection between state intervention and explaining the observed urban premium in a transitioning economy context.